Simultaneous Wavelength and Format Conversions Based on the Polarization-Insensitive FWM in Free-Space Optical Communication Network - Xinning Huang; Yulong Suh; Tao Duan; Hui Hu; Xin Xu; Xiaoping Xie (IEEE Photonics Journal, 2019)
Free-space optical (FSO) network is an effective way to enhance the interoperability and improve the resource utilization of the FSO communication systems. Since the structure is relatively simple and the nodes are not so many, wavelength conversion-based optical circuit switching (WC-OCS) is an appropriate candidate for the FSO network to solve the blocking problem. Meanwhile, format conversion to lower the data rate is also necessary in case the atmospheric channel deteriorates. In this paper, we construct a 3-node FSO network and experimentally investigate the feasibility of simultaneous WC-OCS and format conversion based on straight-lined single-pump four-wave mixing (FWM) process. The bit-error-ratio (BER) results of the on-off key, binary phase-shift keying (BPSK), and quadrature phase-shift keying (QPSK) signals show that comparing to the corresponding back-to-back (B2B) transmission at the reference BER level of ${10^{-7}}$ , power penalties caused by WC-OCS are less than 1-dB for all the three formats. In the format conversion experiment from QPSK to BPSK, the power penalties, comparing to the original BPSK signal after B2B and WC-OCS transmission, are also less than 1 dB at the ${10^{ - 7}}$ reference BER level. Consequently the feasibility and practicability of the FWM-based optical signal processing at FSO network nodes are experimentally validated.